Anesthesia for muscle biopsy to test susceptibility to malignant hyperthermia - Silva,Helga Cristina Almeida da (2019)
Abstract Introduction Malignant hyperthermia is an autosomal dominant pharmacogenetic disorder, characterized by hypermetabolic crisis triggered by halogenated anesthetics and/or succinylcholine. The standard method for diagnosing malignant hyperthermia susceptibility is the in vitro muscle contracture test in response to halothane-caffeine, which requires muscle biopsy under anesthesia. We describe a series of anesthetic procedures without triggering agents in malignant hyperthermia, comparing peripheral nerve block and subarachnoid anesthesia. Method We assessed the anesthetic record charts of 69 patients suspected of malignant hyperthermia susceptibility who underwent muscle biopsy for in vitro muscle contracture in the period of 7 years. Demographic data, indication for malignant hyperthermia investigation, in vitro muscle contracture test results, and surgery/anesthesia/recovery data were analyzed. Results Sample with 34 ± 13.7 years, 60.9% women, 65.2% of in vitro muscle contracture test positive. Techniques used: peripheral nerve blocks — lateral femoral and femoral cutaneous, latency 65 ± 41 min — (47.8%); subarachnoid anesthesia (49.3%), and total venous anesthesia (1.4%). There was 39.4% failure of peripheral nerve block and 11.8% of subarachnoid anesthesia. Adverse events (8.7%) occurred only with subarachnoid blockade (bradycardia, nausea, and transient neurological syndrome). All patients remained in the post-anesthesia care unit until discharge. Age and weight were significantly higher in patients with blockade failure (ROC cut-off point of 23.5 years and 59.5 kg) and blockade failure was more frequent in the presence of increased idiopathic creatine kinase. Conclusion Anesthesia with non-triggering agents has been shown to be safe in patients with malignant hyperthermia susceptibility. Variables such as age, weight, and history of increased idiopathic creatine kinase may be useful in selecting the anesthetic technique for this group of patients.